2005
DOI: 10.1161/circulationaha.105.546465
|View full text |Cite
|
Sign up to set email alerts
|

What a Cardiologist Needs to Know About Patients With Human Immunodeficiency Virus Infection

Abstract: Patient case: A 48-year-old man with human immunodeficiency virus (HIV) infection developed chronic chest pain that started after a bout of pneumonia. He has hypertension and has smoked cigarettes in the past. His current medications include Kaletra and Combivir. His total cholesterol was 331 mg/L, his HDL cholesterol was 27 mg/L, his triglycerides were 935 mg/L, and his LDL cholesterol could not be calculated. How should this patient be evaluated and managed?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 127 publications
(140 reference statements)
3
32
0
5
Order By: Relevance
“…21) Clinically, increasing attention has been paid to carotid IMT. Hsue and co-workers have shown that predictors of increased IMT include older age, higher LDL cholesterol, cigarette pack-years, and hypertension in HIV patients, 22) which is broadly consistent with our results in healthy men. Langlois and colleagues reported that increased carotid IMT was associated with high total cholesterol, LDL cholesterol, as well as non-HDL cholesterol and low HDL cholesterol in subjects aged 35 and 55.…”
Section: Discussionsupporting
confidence: 92%
“…21) Clinically, increasing attention has been paid to carotid IMT. Hsue and co-workers have shown that predictors of increased IMT include older age, higher LDL cholesterol, cigarette pack-years, and hypertension in HIV patients, 22) which is broadly consistent with our results in healthy men. Langlois and colleagues reported that increased carotid IMT was associated with high total cholesterol, LDL cholesterol, as well as non-HDL cholesterol and low HDL cholesterol in subjects aged 35 and 55.…”
Section: Discussionsupporting
confidence: 92%
“…22 Each of these metabolic abnormalities is well documented in HIV-positive patients and may be due to HIV infection or to treatment with drugs such as protease inhibitors as part of highly active antiretroviral therapy (HAART). [23][24][25] In a recent meta-analysis, 15% of HIV-infected patients had osteoporosis, for a pooled odds ratio of 3.7 compared to HIV-negative controls. 26 In a separate study, vitamin D insufficiency (81%) and secondary hyperparathyroidism (26%) were other frequent findings among HIV patients treated with HAART for more than 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 There is thus a persistent inflammatory state in these patients that results in vascular damage and premature atherosclerosis. 19 Some studies have shown a significant increase in non-calcified plaques in HIV patients treated with HAART, which may also be associated with cardiovascular events.…”
Section: Hiv and The Pathophysiology Of Cardiovascular Diseasementioning
confidence: 99%